2008
DOI: 10.1001/archinternmed.2007.33
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes in Patients With Primary Aldosteronism After Treatment

Abstract: Primary aldosteronism is associated with a cardiovascular complication rate out of proportion to blood pressure levels that benefits substantially from surgical and medical treatment in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
325
2
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(357 citation statements)
references
References 36 publications
(46 reference statements)
14
325
2
8
Order By: Relevance
“…Although mineralocorticoid receptor antagonists produced multi-directional anti-inflammatory effects, their monocyte-and lymphocyte-suppressive effects did not increase with time, and cytokine release was higher than in control subjects during the entire observation period. These findings are in disagreement with those of other authors [8][9][10] who observed similar cardiovascular and nephroprotective benefits after adrenalectomy and spironolactone treatment. However, their study populations included both patients with aldosteronoma (most of whom underwent adrenalectomy) and patients with bilateral adrenal hyperplasia (treated with spironolactone), and this fact may explain the differences between our results and their results.…”
contrasting
confidence: 99%
“…Although mineralocorticoid receptor antagonists produced multi-directional anti-inflammatory effects, their monocyte-and lymphocyte-suppressive effects did not increase with time, and cytokine release was higher than in control subjects during the entire observation period. These findings are in disagreement with those of other authors [8][9][10] who observed similar cardiovascular and nephroprotective benefits after adrenalectomy and spironolactone treatment. However, their study populations included both patients with aldosteronoma (most of whom underwent adrenalectomy) and patients with bilateral adrenal hyperplasia (treated with spironolactone), and this fact may explain the differences between our results and their results.…”
contrasting
confidence: 99%
“…[29][30][31][32][33][34][35] A prospective study compared cardiovascular events in 54 PA patients treated by adrenalectomy (unilateral disease) or with spironolactone (unilateral or bilateral disease) with 323 patients with essential hypertension. 36 The composite endpoint was myocardial infarction, stroke, any type of revascularization procedure, and sustained arrhythmia. Its incidence over a mean follow-up of 7.4 years did not differ between patients with treated PA and their controls (who achieved similar BP levels throughout follow-up).…”
Section: Outcomes Of Adrenalectomy In Unilateral Pamentioning
confidence: 99%
“…29,34,85 The benefits of PA treatment were similar for specific drugs and surgery in both studies comparing the incidence of cardiovascular events in treated PA patients and matched controls with essential hypertension. 36,37 The relative glomerular hyperfiltration and microalbuminuria of PA patients are corrected on specific drugs (Figure 1). 40,[44][45][46]50,51,[53][54][55] Spironolactone was found to be less effective than surgery for achieving this end in one study using a fixed low dose (50 mg/day).…”
Section: Outcomes Of Drug-based Treatmentmentioning
confidence: 99%
“…Consequently, treatment objectives include correction for aldosterone hypersecretion or for the excess stimulation of mineralocorticoid receptors (21). In patients with lateralized aldosterone hypersecretion, this goal can be achieved by adrenalectomy and probably by the long-term prescription of MRAs (22), and MRAs provide a specific treatment for PA in patients who are not candidates for surgery.…”
Section: Amiloridementioning
confidence: 99%